Stereotype of crafty statistics: content, causes and consequences - Mikhail V. Karmanov (Статистика и экономика)
The purpose of the study: to consider comprehensively the stereotype of crafty statistics, a phenomenon widely spread in Russia in recent years. It implies that any officially published data supplied by ROSSTAT (Federal State Statistics Service) are not only inadequate and unrealistic, but also deliberately distorted. The paper scrutinizes the content, reasons and possible consequences of crafty statistics.Materials and methods. The paper attempts to unveil the genesis of the stereotype of crafty statistics as a response of civil society to sluggish efforts of government officials and politicians of different levels and ranks to stop declaring slogans and get down to real actions directed at improving living conditions and standards of the broad sectors of the populations. The paper suggests multiple reasons to explore the genesis of the stereotype of crafty statistics, which include complexity of methodology of statistical calculations, overwhelming average indicators, subjectivism in selecting indicators to describe socio-economic situation, data interpretation problems and others.Results. The conducted analysis revealed that it is due to overlay of the above factors that predetermines not only the mass character but also the resilience of this stereotype. Also, low statistical literacy of representatives of various segments of ordinary Russians, representatives of mass media, administration bodies of different level and political beau monde contribute to this phenomenon. The study describes possible negative consequences of the further development of this stereotype leading to serious damage to the government image, which the broad sectors of the population consider the initiator of this statistics, reflecting the improvement of the situation or actions in this direction.Conclusion. The paper reveals risks of any social stereotypes and stereotype of crafty statistics in particular thriving on the lack of trust from the population to any statistics data and turning it into an established negative trend of total distrust to any actions, projects and programs of the current government.